2023
DOI: 10.1155/2023/8392674
|View full text |Cite
|
Sign up to set email alerts
|

Mitigating Postfrying Degradation Factors of Fats and Oils through the Development of Bagasse-Based Adsorbent

Waqar Ahmed,
Muhammad Asim Shabbir,
Rana Muhammad Aadil
et al.

Abstract: The quality of fats and oils is a critical aspect of the food processing industry and consumer health. Fat degradation, particularly through oxidation, impacts various quality parameters, including color, taste, flavor, aroma, quality, and appearance. To address this issue, a study was conducted using five degraded fats/oil (DF/O) commodities as the target for an adsorption process. These commodities were chosen because of their high level of degradation by-products. The study used sugarcane bagasse (SCB) to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 25 publications
0
0
0
Order By: Relevance
“…The concentration of adsorbents, particle size, types of oils, and adsorbents, among other factors, all affected the performance of adsorbents in previous studies involving oil regeneration. ,,, However, in the current study, FE demonstrated the best performance in terms of reducing FFA %, as it reduced the maximum amount of FFA % of the edible oils. FFA, being polar molecules since they are carboxylic groups (–COOH) with a polar side, have been adsorbed for their attraction to hydrophilic-natured adsorbents …”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The concentration of adsorbents, particle size, types of oils, and adsorbents, among other factors, all affected the performance of adsorbents in previous studies involving oil regeneration. ,,, However, in the current study, FE demonstrated the best performance in terms of reducing FFA %, as it reduced the maximum amount of FFA % of the edible oils. FFA, being polar molecules since they are carboxylic groups (–COOH) with a polar side, have been adsorbed for their attraction to hydrophilic-natured adsorbents …”
Section: Resultsmentioning
confidence: 99%
“…Although there are very few data points available for rice bran oil and palm olein oil regeneration, Bhattayacharya et al showed the better effectiveness of MgO and AC in removing secondary oxidation products from sunflower and soybean oil . Similarly, Nuru and Getachew reported the highest effectivity of MgO and ash to reduce PV in niger seed oil, and Hidayatullah and Bangash stated the better activity of MgO and AC in enhancing the quality of fried Silybum marianum oil. , The reduction of PV can be explained by the Freundlich isotherm, which measures the overall effectivity of the adsorbent considering the variety of the adsorbent surface and different ions entrapped in the adsorbent pores …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations